Aligned Fingolimod-Releasing Electrospun Fibers Increase Dorsal Root Ganglia Neurite Extension and Decrease Schwann Cell Expression of Promyelinating Factors - Puhl, Devan L.; Funnell, Jessica L.; D’Amato, Anthony R.; Bao, Jonathan; Zagorevski, Dmitri V.; Pressman, Yelena; Morone, Daniel; Haggerty, Agnes E.; Oudega, Martin; Gilbert, Ryan J. (Frontiers in Bioengineering and Biotechnology, 2020)
Researchers are investigating the use of biomaterials with aligned guidance cues like those provided by aligned electrospun fibers to facilitate axonal growth across critical length peripheral nerve defects. To enhance regenerative outcomes further, these aligned fibers can be designed to provide local, sustained release of therapeutics. The drug fingolimod improved peripheral nerve regeneration in preclinical rodent models by stimulating a pro-regenerative Schwann cell phenotype and axonal growth. However, systemic delivery of fingolimod for nerve repair can lead to adverse effects, so it is necessary to develop a means of providing sustained delivery of fingolimod local to the injury. Here, we created aligned fingolimod-releasing electrospun fibers that provide directional guidance cues in combination with local, sustained release of fingolimod to enhance neurite outgrowth and stimulate a pro-regenerative Schwann cell phenotype. Electrospun fiber scaffolds were created by blending fingolimod into poly(lactic-co-glycolic acid) (PLGA) at a w/w% (drug/polymer) of 0.0004%, 0.02%, or 0.04%. We examined the effectiveness of these scaffolds to stimulate neurite extension in vitro by measuring neurite outgrowth from whole and dissociated dorsal root ganglia (DRG). Subsequently, we characterized Schwann cell migration and gene expression in vitro. Results show that drug-loaded PLGA fibers released fingolimod for 28 days, which is the longest reported release of fingolimod from electrospun fibers. Further, the 0.02% fingolimod-loaded fibers enhanced neurite outgrowth from whole and dissociated DRG neurons, increased Schwann cell migration, and reduced Schwann cell expression of promyelinating factors. The in vitro findings show the potential of the aligned fingolimod-releasing electrospun fibers to enhance peripheral nerve regeneration and serve as a basis for future in vivo studies.